The interrelationship of intellectual capital disclosure, IPO underpricing and board characteristics: ASEAN evidence. - Nimtrakoon, Sirinuch; Tayles, Michael (SOUTHEAST ASIAN JOURNAL OF ECONOMICS, 2024)
This research investigates the relationships between board characteristics, intellectual capital (IC) disclosure and the level of IPO underpricing in the context of ASEAN countries. Content analysis of IPO prospectuses was employed for 192 ASEAN companies which underwent IPO listing between 2014 and 2017 a period straddling the creation of the ASEAN Economic Community (AEC). The influence of board characteristics on underpricing is shown to be in the appropriate direction but not statistically significant. Of the four board characteristics investigated, three have statistically significant direct influence on the extent of IC disclosure. The research demonstrates the importance of IC disclosure within ASEAN, on which we have relatively limited prior knowledge, however the results demonstrate a relatively low level of IC disclosure in the ASEAN with insufficient impact to mitigate the information asymmetry gap and impact the level of underpricing. Regulators may need to promote greater IC disclosure before the level of underpricing can be influenced.